EQUILIBRIUM AND KINETIC STUDIES ON THE REMOVAL OF HEAVY METAL IONS WITH NATURAL LOW-COST ADSORBENTS - Varank, Gamze; Demir, Ahmet; Bilgili, M. Sinan; Top, Selin; Sekman, Elif; Yazici, Senem; Erkan, Hanife Sari (TECHNICAL UNIV WROCLAW, 2014)
Adsorption isotherms and kinetics of the removal of heavy metal ions (Ni, Pb, Zn) from aqueous solutions by natural adsorbents (zeolite, bentonite, clay) were investigated in a lab-scale batch study. The effect of various parameters such as adsorbent dosage, initial concentration of heavy metal ions, temperature, and agitation time were studied to optimise the conditions. Under those optimized conditions (180 rpm agitation rate, 120 min agitation time, pH 4.0, 298 K, 100 mg/dm(3) initial adsorbate concentration), the removal percentages of heavy metal ions for natural adsorbents have been determined. The adsorption mechanisms and characteristic parameters of the process were analyzed by two and three parameter isotherm models (Langmuir, Freundlich, Temkin, Redlich-Peterson, Toth and Sips), and kinetic models (Lagergren's pseudo-first order, Ho and McKay's pseudo-second order). Adsorption thermodynamics of heavy metal ions (changes of standard enthalpy, entropy and free energy) on zeolite, bentonite and clay were also studied at 298, 318 and 338 K.
Keywords: ACTIVATED CARBON; ADSORPTION; SORPTION; 2-PARAMETER; ZINC; BIOSORPTION; ISOTHERMS; BENTONITE; EQUATIONS; ZEOLITE; Engineering